Carotidynia Possibly due to Localized Vasculitis in a Patient with Latent Mycobacterium tuberculosis Infection. (2nd December 2013) - Cassone, Giulia; Colaci, Michele; Giuggioli, Dilia; Manfredi, Andreina; Sebastiani, Marco; Ferri, Clodoveo
Abstract : Carotidynia is a syndrome characterized by tenderness of the carotid artery near the bifurcation due to numerous, heterogeneous causes. Here we reported the case of a 31-year-old Moroccan woman with right-sided neck pain and tenderness with irradiation to ipsilateral ear, eye, and occipital region. Clinical symptoms and imaging findings were suggestive of primary variant of carotidynia syndrome. In particular, color-Doppler ultrasonography revealed a concentric wall thickening of the distal common carotid artery, while thoracic magnetic resonance showed localized perivascular enhancement of the soft tissue in the right medial-distal common carotid artery in T1-weighted images, without intraluminal diameter variation. Moreover, careful clinicoserological and imaging investigations (cranial, cervical, and thoracic angiocomputed tomography and magnetic resonance) excluded well-known disorders potentially responsible for carotidynia syndrome. The patient was scarcely responsive to nonsteroidal anti-inflammatory drugs, but clinical symptoms resolved after three months. Of interest, the patient showed latent Mycobacterium tuberculosis infection (positive tuberculosis interferon-gamma release assay; QuantiFERON-TB Gold); this finding suggested a possible triggering role of mycobacterial antigens in the immune-mediated mechanism responsible for localized carotid injury.